Efektivitas pintasan pemberian warna klasifikasi utama pada nomor panggil koleksi dalam mengoptimalkan kegiatan shelving - Firdaus, Yusrizal Adytia (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. Book shelving is considered challenging in libraries with a large physical collection without a clear auxiliary shortcut. This research aims to understand the effectiveness of the main classification color shortcut on the collection call number. Data Collection Methods. The research was conducted by adopting Descriptive Quantitative method through Unsequenced and Comparative approaches based on a case study at the Ministry of Education and Culture Library, Republic of Indonesia. Data Analysis. The data analysis used in this research was Analysis of Variance (ANOVA). Results and Discussion. The results show that testing shelving details, the reference shelf collection scored 33%, while the fiction shelf collection scored less, showing 26.1%. In the shelving search test, twenty reference shelf collections were found in 1,333 seconds, while the fiction shelf collection took 1,669 seconds. Conclusion. Having the color of the classification number identifier is proven to support convenience in doing shelving detail activities, as well as searching for collections on the shelf even with a large number. Future research is expected to group the color numbers 0-9 based on the type and characteristics of color contrast as the identity of classification numbers for collection call numbers.